PENGARUH AUDIT FEE, JASA SELAIN AUDIT, PROFIL K.A.P, HUBUNGAN AUDIT LAMA K.A.P DENGAN KLIEN TERHADAP INDEPENDENSI AUDITOR K.A.P DI SURABAYA - Rudi Pratomo; Desy Indah Lestari (BALANCE: Economic, Business, Management and Accounting Journal, 2010)
This study aims to determine any factors that may affect the independence of public accountants in the audit by the public accountant's office inSurabaya. Analysis technique used was simple linear regression model analysis and multiple linear regression using SPSS version 11.0 aids.This research may prove that the audit fee, other than audit services provided by public accounting firms to the same client at the same time, the profile of public accounting firms, and the latter is the length of the relationship between the audit client with a public accounting firm jointly influential against the independence of public accountants. From the test results of partially performed, proved all of these factors also affect the independence of public accountants. Key words: Independence, Audit Fee, Other Services, Profiles KAP, length of relationship.